2011
DOI: 10.1111/j.1532-5415.2011.03663.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cohort Study of Geriatric Syndromes Among Older Medical Patients Admitted to Acute Care Hospitals

Abstract: Geriatric syndromes were highly prevalent. Many patients did not return to their premorbid function and acquired new syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
118
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(127 citation statements)
references
References 49 publications
3
118
2
2
Order By: Relevance
“…1 These syndromes are highly prevalent among older patients admitted to acute-care hospitals 2,3 and often add complexity to the clinical status of hospitalized older adults with multiple comorbid conditions. 4 In the English National Health Service (NHS), the proportion of older people admitted to acute-care hospitals with geriatric syndromes has increased dramatically.…”
mentioning
confidence: 99%
“…1 These syndromes are highly prevalent among older patients admitted to acute-care hospitals 2,3 and often add complexity to the clinical status of hospitalized older adults with multiple comorbid conditions. 4 In the English National Health Service (NHS), the proportion of older people admitted to acute-care hospitals with geriatric syndromes has increased dramatically.…”
mentioning
confidence: 99%
“…1 Indeed, besides the negative effect of the acute event, hospitalization itself might represent an additional stressor 2 in terms of environmental hazard, reduced caloric intake, low physical activity or prolonged bed rest, depressed mood, and social isolation; furthermore, many older inpatients experience new geriatric syndromes and worsening of existing syndromes during hospitalization. 3 Decline in health status during hospitalization has important consequences in terms of quality of life and healthcare utilization as it has been associated with the risk of longer hospital stay, institutionalization, and mortality. 4,5 Availability of objective and standardized tools to assess and track health status changes during hospitalization is of great importance for appropriate management and to properly monitor the effect of medical therapy.…”
mentioning
confidence: 99%
“…Literature related to the development of incontinence within acute care settings for elderly people with cognitive impairment is limited (Lakhan et al, 2011;Price, 2011). The most closely related quantifiable data to this study, is a prospective cohort study by Lakhan et al (2011Lakhan et al ( , p. 2007 which found that many patients over 70 whilst in hospital ''acquired new syndromes'' including incontinence, and did not return to their premorbid function.…”
Section: Discussionmentioning
confidence: 84%